2013
DOI: 10.1111/evj.12039
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for large colon volvulus in theUK

Abstract: Summary 6Reasons for performing study: Risk factors for large colon volvulus (LCV) in the horse have 7 not been previously reported. Knowledge of these risk factors may allow the introduction of 8 measures that could be taken to minimise the incidence of LCV. 9Objectives: To investigate risk factors for LCV in the horse. 10Methods: A prospective, multi-centre, un-matched case-control study was conducted over a and to provide evidence-based advice to owners of these horses. 29

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 48 publications
(66 reference statements)
1
38
1
Order By: Relevance
“…), but the sudden increase in potential intra‐abdominal space following foaling may play a part in development of LCV (Suthers et al . ). This would be the reverse of a loss of space with gastric impaction, but a net change in intra‐abdominal space may ultimately prove to be a common factor in LCV development.…”
mentioning
confidence: 97%
“…), but the sudden increase in potential intra‐abdominal space following foaling may play a part in development of LCV (Suthers et al . ). This would be the reverse of a loss of space with gastric impaction, but a net change in intra‐abdominal space may ultimately prove to be a common factor in LCV development.…”
mentioning
confidence: 97%
“…Risk factors for LCV in mature horses include the post‐partum period, increasing horse height, history of multiple episodes of colic, reduced pasture access and hay feeding (Suthers et al . ). However, these factors do not explain the development of LCV in a neonatal foal.…”
Section: Discussionmentioning
confidence: 97%
“…Provision of hay and specific types of hay have previously been identified to alter the risk of colic and increase the likelihood of specific forms of colic such as ileal impactions [28] and large colon volvulus [29]. Haylage has not to the authors’ knowledge been identified as a risk factor for colic in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing time spent stabled and reduced time spent out at pasture have been identified as factors that increase the risk of colic in previous studies [14,16,29,32]. Whilst duration of time spent stabled at other times of the year were not significantly associated with risk of colic, the autumn months would generally be considered to be a time when management changes such as feeding and stabling change in the UK, dependent on a number of factors such as prevailing weather conditions and pasture available for grazing.…”
Section: Discussionmentioning
confidence: 99%